1993
DOI: 10.1128/aac.37.11.2298
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, comparative study of rufloxacin once daily versus amoxicillin three times a day in treatment of outpatients with exacerbations of chronic bronchitis

Abstract: In a double-blind, randomized, multicenter study, the efficacy and safety of two dosage schedules of rufloxacin once daily were compared with those of amoxicillin three times a day in the treatment of 192 outpatients with exacerbations of chronic bronchitis. Rufloxacin was given as a single oral dose of 400 mg on day 1 and single daily doses of 200 mg on the subsequent 9 days (n = 64) or as 300 mg on day 1 and then 150 mg daily for 9 days (n = 63); amoxicillin was given as 500 mg orally three times a day for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Furthermore, central nervous system reactions were the most commonly reported adverse effects in ofloxacin's postmarketing studies performed in Germany (9). With rufloxacin, 20% of patients reported one or more adverse events, a figure similar to those reported by other authors (14 to 21%) after a single dose or 7 to 14 days of treatment (14,17,20). This figure is heavily influenced by central nervous system reactions which were reported by 12% of patients, similar to the rate reported (13%) in another trial (14) but much higher than the one observed by Klietman et al (17), who only reported 5 cases of this kind of adverse event among 127 patients who were treated with rufloxacin for 10 days.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, central nervous system reactions were the most commonly reported adverse effects in ofloxacin's postmarketing studies performed in Germany (9). With rufloxacin, 20% of patients reported one or more adverse events, a figure similar to those reported by other authors (14 to 21%) after a single dose or 7 to 14 days of treatment (14,17,20). This figure is heavily influenced by central nervous system reactions which were reported by 12% of patients, similar to the rate reported (13%) in another trial (14) but much higher than the one observed by Klietman et al (17), who only reported 5 cases of this kind of adverse event among 127 patients who were treated with rufloxacin for 10 days.…”
Section: Discussionsupporting
confidence: 88%
“…Steady high concentrations (60 ,ug/ml) of rufloxacin are attained in urine up to 72 h following administration of a single 400-mg dose (37). In view of its pharmacokinetic profile, it can be used once daily for the treatment of urinary (5,24) and respiratory tract (20) infections. It is metabolized at a low level.…”
mentioning
confidence: 99%
“…Available data from clinical trials suggest that rufloxacin, besides its efficacy against other infectious diseases such as urinary tract infections (10,20), is a suitable drug for the treatment of patients with chronic obstructive pulmonary infections (11,23,30). These patients often require theophylline, a bronchodilator, for the treatment of bronchospasms.…”
mentioning
confidence: 99%